Targeting Mcl-1 by AMG-176 During Ibrutinib and Venetoclax Therapy in Chronic Lymphocytic Leukemia - Yi, Xue; Jain, Nitin; Iles, LaKesla R.; Ayres, Mary L.; Wierda, William G.; Gandhi, Varsha (Frontiers in Oncology, 2022)
B-cell receptor (BCR) signaling pathway and Bcl-2 family prosurvival proteins, specifically Bcl-2 and Mcl-1, are functional in the pathobiology of chronic lymphocytic leukemia (CLL). A pivotal and apical molecule in the BCR pathway is Bruton’s tyrosine kinase (BTK). Together, BTK, Bcl-2, and Mcl-1 participate in the maintenance, migration, proliferation, and survival of CLL cells. Several ongoing and published clinical trials in CLL reported high rates of remission, including undetectable measurable residual disease (u-MRD) status with combined BTK inhibitor ibrutinib and Bcl-2 antagonist, venetoclax. While the majority of patients achieve complete remission with undetectable-measurable residual disease, at least one third of patients do not achieve this milestone. We hypothesized that cells persistent during ibrutinib and venetoclax therapy may be sensitive to combined venetoclax and Mcl-1 inhibitor, AMG-176. To test this hypothesis, we took peripheral blood samples at baseline, after Cycle 1 and Cycle 3 of ibrutinib monotherapy, after one week and 1 cycle of ibrutinib plus venetoclax therapy. These serial samples were tested for pharmacodynamic changes and treated in vitro with AMG-176 or in combination with venetoclax. Compared to C1D1 cells, residual cells during ibrutinib and venetoclax treatment were inherently resistant to endogenous cell death. Single agent exposure induced some apoptosis but combination of 100 nM venetoclax and 100 or 300 nM of AMG-176 resulted in 40-100% cell death in baseline samples. Cells obtained after four cycles of ibrutinib and one cycle of venetoclax, when treated with such concentration of venetoclax and AMG-176, showed 10 – 80 % cell death. BCR signaling pathway, measured as autophosphorylation of BTK was inhibited throughout therapy in all post-therapy samples. Among four anti-apoptotic proteins, Mcl-1 and Bfl-1 decreased during therapy in most samples. Proapoptotic proteins decreased during therapy. Collectively, these data provide a rationale to test Mcl-1 antagonists alone or in combination in CLL during treatment with ibrutinib and venetoclax.